A nebulised antitumour necrosis factor receptor-1 domain antibody in patients at risk of postoperative lung injury: A randomised, placebo-controlled pilot study. Issue 11 (November 2020) - Ryan, James; Bayliffe, Andrew I.; McAuley, Daniel F.; Yeung, Joyce; Thickett, David R.; Howells, Phillip A.; O'Donnell, Ciara; Vassallo, Arlette M.; Wright, Tracey J.; McKie, Elizabeth; Hardes, Kelly; Summers, Charlotte; et al.
Abstract : BACKGROUND: Tumour necrosis factor receptor 1 (TNFR1) signalling mediates the cell death and inflammatory effects of TNF-α. OBJECTIVE: The current clinical trial investigated the effects of a nebulised TNFR1 antagonist (GSK2862277) on signs of lung injury in patients undergoing oesophagectomy. DESIGN: Randomised double-blind (sponsor unblind), placebo-controlled, parallel group study. SETTING: Eight secondary care centres, the United Kingdom between April 2015 and June 2017. PATIENTS: Thirty-three patients undergoing elective transthoracic oesophagectomy. INTERVENTIONS: Patients randomly received a single nebulised dose (26 mg) of GSK2862277 ( n  = 17) or placebo ( n  = 16), given 1 to 5 h before surgery; 14 and 16, respectively competed the study. MAIN OUTCOME MEASUREMENTS: Physiological and biochemical markers of lung injury, pharmacokinetic and safety endpoints were measured. The primary endpoint was the change from baseline in pulmonary vascular permeability index (PVPI) at completion of surgery, measured using single-indicator transpulmonary thermodilution. Adjusted point estimates and 95% credible intervals (analogous to conventional confidence intervals) were constructed for each treatment using Bayesian statistical models. RESULTS: The mean change (with 95% credible intervals) from baseline in PVPI on completion of surgery was 0.00 (−0.23, 0.39) in the placebo and 0.00 (−0.24, 0.37) in the GSK2862277 treatment groups. There were no significant treatment-related differences in PaO2 /Fi O2 or Sequential Organ Failure Assessment score. Levels of free soluble TNFR1, Macrophage Inflammatory Protein-1 alpha and total protein were significantly reduced in the bronchoalveolar lavage fluid of patients treated with GSK2862277 (posterior probability of decrease with GSK2862277 vs. placebo:≥0.977; equivalent to P  < 0.05). The frequency of adverse events and serious adverse events were distributed evenly across the two treatment arms. CONCLUSION: Pre-operative treatment with a single 26 mg inhaled dose of GSK2862277 did not result in significantly lower postoperative alveolar capillary leak or extra vascular lung water. Unexpectedly small increases in transpulmonary thermodilution-measured PVPI and extra vascular lung water index at completion of surgery suggest less postoperative lung injury than historically reported, which may have also compromised a clear assessment of efficacy in this trial. GSK2862277 was well tolerated, resulted in expected lung exposure and reduced biomarkers of lung permeability and inflammation. TRIAL REGISTRATION: clinicaltrials.gov: NCT02221037. Abstract : Supplemental Digital Content is available in the text